Applying unmanned aerial vehicles (UAVs) to map shrubland structural attributes in northern Patagonia, Argentina - Gonzalez Musso, Romina F. (2020)
Fil: Gonzalez Musso, Romina F. Universidad Nacional del Comahue. Argentina.